Media Use in Digital Everyday Life. - Ytre-Arne, Brita. (Emerald Points Series, 2023)
The ebook edition of this title is Open Access and freely available to read online. Filling a gap between classic discussions on everyday media use and recent studies of emergent technologies, this book untangles how media become meaningful to us in the everyday, connecting us to communities and publics.